Sommeil et course au large en solitaire : comportements des coureurs et étude de faisabilité d’un « agenda interactif de sommeil » - Denis Theunynck; Rémy Hurdiel; Thierry Pezé; Xavier Estruch; Gilles Bui-Xuân (Perspectives Interdisciplinaires sur le Travail et la Santé)
Solo sailing racing associates intense and prolonged (10 to 100 days) physical and cognitive effort under extreme conditions. It involves split sleep and short rest periods distributed throughout the day and night. These difficulties are mentioned to explain incidents, accidents and changes in performance.This study identifies the strategies used by nine of the best solo skippers to prepare and then manage these constraints during a race. It then follows one of the skippers for a one-hundred-day non-stop solo race around the world.Based on these observations, it was proposed to one skipper that he test an interactive “sleep” diary so that he could learn how to manage his periods of sleep in an optimal way during a race.This study shows that the subjects are aware of the importance of managing their periods of rest, but use few sleep preparation and management strategies before and during their race. They undergo an adaptation period to these extreme conditions for 24 to 72 hours and then experience periods of extreme fatigue with hallucinations. This fatigue has consequences on their performance, but also on accidentology, which seems much greater with a possible time lag of up to 72 hours after an excessive sleep debt. Laboratory tools, which could provide interesting information only with continuous use, are very difficult to use under these extreme conditions.Under these circumstances, an interactive sleep diary, used by the subject to record and manage the distribution and duration of his periods of sleep, seems to be an individual solution for managing the wake and sleep cycle. A critical sleep-debt threshold may exist, below which a higher frequency of incidents and accidents would be observed. This preliminary study will be followed by larger scale observations in order to validate the “interactive sleep diary” as a routine descriptive and learning tool.